Improving Vowel Articulation through Using Videos in English Foreign Language Classroom Case of Fourth Year Pupils at Abd El Wahed NouarBen Ali Middle School in Souk-Ahras - Ibtissem Gouasmia (My University, 2022)
ABSTRACT The current study is about the use of videos to improve vowels articulation, it is focused on theactivity-oriented approach because pronunciation is very essential when we teach or learn a foreign language. So, this study shows that the use of audio-visual aids such as a video may help the pupils to pronounce and articulate vowels correctly .In addition, the aim behind this study is to give pupils opportunity to learn from his/her mistakes and to identify that the use of video in EFL classroom is very beneficial. This research is conducted with fourth year pupils at Abd El Wahed Nouar middle school in Souk Ahras, in order to test the main hypothesis which suggests that the use of video in EFL classrooms improves vowels articulation. The researcher has done an experiment by selecting randomly two groups of fourth year pupils at( Abd El Wahed Nouar Ben Ali) middle school. The first group which is the experimental group, was taught a lesson with the use of videos while the second one which is the Control group was taught the same lecture without the use of that tool. The obtained results showed that the Experimental group achieve a considerable improvement when pronouncing vowels rather than the Control group. Thus, the use of video has a positive impact on teaching pronunciation especially vowels. ---------------- الملخص تدور الدراسة الحالية حول استخدام الفيديو لتحسين نطق أحرف العلة و التركيز على المنهج الموجه نحو نشاط لان النطق عملية ضرورية للغاية عند تدريس أو تعليم لغة أجنبية لدلك هذه الدراسة توضح أن استعمال الفيديو يمكن أن يساعد التلاميذ في نطق أحرف العلة و التعبير عنها بشكل صحيح إضافة إلى ذلك الهدف من هذه الدراسة هو إعطاء التلاميذ فرصة لتعلم من أخطائهم وتبين أن استخدام الفيديو في قسم اللغة الأجنبية مفيد للغاية . أجرى هذا البحث على تلاميذ السنة الرابعة في المتوسطة عبد الواحد بن نوار سوق أهراس من اجل اختبار الفرضية التي تشير إلى أن استخدام الفيديو في الفصل الدراسي يحسن نطق حروف العلة قد تم استخدام تجربة تدور حول الاختيار العشوائي لمجموعتين المجموعة الأولى هي المجموعة التجريبية والتي تدرس الدرس باستخدام الفيديو بينما المجموعة الأخرى هي المجموعة الضابطة التي درست نفس الدرس دون استخدام الأداة التحفيزية . استندت التجربة إلى المراحل التالية بدءا من الاختبار القبلي مرحلة العلاج و الاختبار البعدي بعد الحصول على نتائج كلا الاختبارين و بعد ذلك قمنا بحساب و مقارنة وسائل الاختبار القبلي والبعدي للمجموعتين اللتين تم الحصول عليهما من نتائج . أن المجموعة التجريبية تحقق تحسنا ملحوظ في نطق أحرف العلة بدلا من المجموعة الضابطة بناءا على هذه النتائج تبين أن استخدام الفيديو تأثير ايجابي على تعليم النطق خاصة أحرف العلة